The geochemistry, mineralogy and igneous petrology of some fracture zone basalts from the southern Mid-Atlantic Ridge - Van Heerden, Leon (Department of Oceanography, 2024)
The compositional variation in a suite of oceanic basalts dredged from a fracture zone transecting the Mid-Atlantic Ridge at 54°S is quantitatively evaluated in terms of fractional crystallization and crystal accumulation models. Bulk rock chemistry and petrography are used to classify the samples into four distinct groups; an evolved sparsely plagioclase phyric suite (Group A), a less evolved sparsely plagioclase phyric suite (Group B), an olivine phyric suite (Group C) and a highly plagioclase phyric suite (Group D). The Group A basalts are characterised by their evolved nature (Mg# = 52.8-59.4) and by relatively high Tio2 (1.89 - 2.15 wt%) and FeO (9.77 - 10.59 wt%) contents when compared to the Group B basal ts. These are characterised by Tio2 contents of between 1.08 and 1.63 wt% and by elevated Al 2o 3 (15.85 - 16.76 wt%) and Cao ( 11. 43 - 12. 27 wt%) contents. The Group c basal ts are uniquely identified by their olivine phyric nature and consequently high Mgo concentrations (8. 39 - 15. 54 wt%) and by having high to extremely high Cr and Ni contents ( 502 - 1079 ppm, 173 - 653 ppm respectively). The Group D basalt is identified by its pl)gioclase phyric nature, its high Mg# (70.0) and by the extremely high Al 2o 3 (19.35 wt%) and Cao (13.17 wt%) concentrations. Whole rock major and trace element variations in conjunction with a mineralogical study of the major mineral phases present (olivine; plagioclase; spinel) are used to place constraints on the genetic relationships between the different basalt groups. ii Trace element ratios and profiles, the distribution of NiO in olivines and Ba-Zr relationships are used to identify 4 distinct parental magmas. Consideration of Fe-Mg partitioning between olivine and the host rock is used to identify possible liquid compositions. Such considerations indicate that the olivine phyric Group C sample represent olivine ( + minor Cr-spinel) enriched magmas, derived from a less MgO rich parental magma. Fe-Mg partitioning into plagioclase is used to infer that the highly plagioclase phyric Group D sample represents a partial plagioclase cumulate. Least squares mixing calculations indicate that compositional variations in the Group A basal ts cannot be explained by the simple closed system fractional crystallization of olivine and plagioclase from the least evolved sample. Group B compositional variation may be explained by up to 6.58% olivine, 22. 20% plagioclase and 9. 42% clinopyroxene fractionation. The Group C basalts may all be related to one of the least magnesian Group C samples by the accumulation of up to 17.05% olivine plus minor Cr-spinel. It is proposed that basalts from this 54"S fracture zone evolved to their present compositions in a series of small, ephemeral crustal magma chambers. Unlike many basalts from this region of "' the Southern Mid-Atlantic Ridge (SMAR), their source regions show no evidence of geochemical enrichment, and these basalts have the trace element characteristics of normal depleted MORB. Within the model proposed by le Roex et al (1987) for the evolutionary history of this region of the S~..AR, these basalts iii are held to represent normal depleted MORB, unaffected by the either the Bouvet hot spot to the south or the Shona hotspot to the northwes